Use of Pumpkin and Its Effect on Quality in Ice Cream Production - Yıldız, Ayşe; Demir, Pelin; Arslan, Ali (My University, 2020)
This study was conducted to investigate the effect of pumpkin, ginger, cinnamon, and coconut on the quality ofice cream (sensory. chemical and microbial). For this purpose. 4 groups ice cream were made and were stored at -18 °C. Samples were subjected to microbiological (total aerobic mesophile bacteria. yeast. and mold). chemical(dry matter. non-fat dry matter. oil and pH) and sensory (color and appearance. structure and consistency. tasteand smell) analysis on days 0th. 10th. 20th and 30th of the storage. Statistically significant differences were foundbetween the groups in terms of dry matter. non-fat dry matter and fat values (p <0.05). As a result. it is shownthat the production of ice cream with quite low sugar which makes the product more dietetic and highlynutritious. and it was detected that the ice-creams could maintain their quality for at least 30 days at -18 °C.
Keywords: Gıda Bilimi ve Teknolojisi